2020
DOI: 10.1371/journal.pone.0242818
|View full text |Cite
|
Sign up to set email alerts
|

On the nature of eye-hand coordination in natural steering behavior

Abstract: Eyes and hand movements are known to be coordinated during a variety of tasks. While steering a vehicle, gaze was observed to be tightly linked with steering wheel angle changes over time, with the eyes leading the hands. In this experiment, participants were asked to drive a winding road composed of bends with systematically manipulated radii of curvature, under regular and automatic steering conditions. With automatic steering, the vehicle followed the road, but the steering wheel and participants hands did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 58 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…To pursue this issue, drivers' eye movements have been used as an indicator of the cognitive processes engaged while driving (Lappi & Mole, 2018), including when driving with automation (Mars & Navarro, 2012;Navarro et al, 2021Navarro et al, , 2020Navarro et al, , 2019 or even during the transition of control from passive to active driving (see Deniel & Navarro, 2023 for a review). Although several neuroimaging studies have been carried out on real and simulated driving, under a variety of experimental conditions (see Ware et al, 2020 for a review), only sparse information about the brain activity engaged during passive driving compared to active driving is available (Sakihara et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…To pursue this issue, drivers' eye movements have been used as an indicator of the cognitive processes engaged while driving (Lappi & Mole, 2018), including when driving with automation (Mars & Navarro, 2012;Navarro et al, 2021Navarro et al, , 2020Navarro et al, , 2019 or even during the transition of control from passive to active driving (see Deniel & Navarro, 2023 for a review). Although several neuroimaging studies have been carried out on real and simulated driving, under a variety of experimental conditions (see Ware et al, 2020 for a review), only sparse information about the brain activity engaged during passive driving compared to active driving is available (Sakihara et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Both studies showed that nearly all the fixations were primarily allocated in a task-oriented manner. Further studies investigated eye movements under a plethora of natural conditions while walking (Matthis et al, 2018), driving (Mars and Navarro, 2012; Sullivan et al, 2012; Navarro et al, 2020), hand-washing (Pelz and Canosa, 2001), hitting a ball (Land and McLeod, 2000), and free exploration (Schumann et al, 2008). These experiments in naturalistic settings have revealed several distinct functions of eye movements during habitual everyday tasks.…”
Section: Introductionmentioning
confidence: 99%
“…An important aspect is that visual attention can guide behaviors (Payne et al, 2017). Some studies have shown that saccade to a target occurs immediately before goal-directed movements occur (Johansson et al, 2001; Navarro et al, 2020). Welsh et al (1999) found that when a target and a distractor were presented in the same scene, manual movements were attracted to the distractor location.…”
mentioning
confidence: 99%